Bacterial lipopolysaccharide protects the retina from light-induced damage - Bordone, Melina Paula (2012)
Light-induced damage is a widely used model to study retinal degeneration. We examined whether bacterial lipopolysaccharide (LPS) protects the retina against light-induced injury. One day before intense light exposure for 24 h, rats were intravitreally injected with LPS in one eye and vehicle in the contralateral eye. At several time points after light exposure, rats were subjected to electroretinography and histological analysis. Bax, Bcl-xL, p-Akt, and p-Stat3 levels were assessed by Western blotting, and retinal thiobarbituric acid reactive substances levels were measured as an index of lipid peroxidation. One group of animals received injections of dexamethasone, aminoguanidine (an inducible NOS inhibitor), 5-hydroxydecanoic acid (a mitochondrial K+/ATP channel blocker), or wortmannin [a phosphoinositide-3-kinase (PI3K) inhibitor] in order to analyze their effect on the protection induced by LPS. LPS afforded significant morphologic and functional protection in eyes exposed to intense light. Light damage induced an increase in mitochondrial Bax/cytoplasmic Bax ratio, and lipid peroxidation which were prevented by LPS. Dexamethasone and wortmannin (but not aminoguanidine or 5-hydroxydecanoic acid) prevented the effect of LPS. Moreover, wortmannin prevented the effect of LPS on p-Akt levels. These results indicate that LPS provides retinal protection against light-induced stress, probably through a PI3K/Akt-dependent mechanism.